Origin, Evolution, Breeding, and Omics of Chayote, an Important Cucurbitaceae Vegetable Crop - Pu, Yu-Ting; Luo, Qing; Wen, Lin-Hong; Li, Yu-Rong; Meng, Ping-Hong; Wang, Xiao-Jing; Tan, Guo-Fei (Frontiers in Plant Science, 2021)
Chayote (Sechium edule), a member of the Cucurbitaceae family, is cultivated throughout tropical and subtropical regions of the world and utilized in pharmaceutical, cosmetic and food industries because it is an excellent source of minerals, dietary fibers, protein, vitamins, carotenoids, polysaccharides, phenolic and flavonoid compounds, and other nutrients. Chayote extracts process various medicinal properties, such as anti-cardiovascular, antidiabetic, antiobesity, antiulcer and anticancer properties. With the rapid advancements of molecular biology and sequencing technology, studies on chayote have been carried out. Research advances, including molecular makers, breeding, genomic research, chemical composition, and pests and diseases, regarding chayote are reviewed in this paper. Future exploration and application trends are briefly described. This review provides a reference for basic and applied research on chayote, an important Cucurbitaceae vegetable crop.